Evaluating The Role Of Policy Interventions In Enhancing Msme Access To Bank Financing (Journal of Namibian Studies : History Politics Culture, 2023)
The paper explores the critical role that policy interventions have in improving and facilitating Micro, Small, and Medium-Sized Enterprises' (MSMEs') access to bank finance. MSMEs are vital to the global economy since they generate a large number of jobs, boost GDP, and encourage innovation. Nonetheless, emerging businesses frequently face difficulties securing sufficient funding, especially from conventional banking institutions. Their growth and potential are severely limited by the inadequate availability of credit. In this study, we examine how company and entrepreneurial characteristics affect the use of debt (bank loans) for investment financing by small and medium-sized firms (SME's). Data was acquired through interviews conducted with 200 SME's in India using a self-organized questionnaire. Using the linear regression econometric model as a foundation, Important variables that affect the growth of debt-financed investments are highlighted. The findings show that there is a relationship between the company's age, size, business plan, industry, number of owners, and funding sources and the expansion of investments funded by India 's banks. Consequently, research findings indicate that the One of the key factors influencing the investment is having access to bank loans or other external funding sources.